HUBUNGAN SELEKSI SDM DENGAN PRODUKTIVITAS KERJA PERAWAT PELAKSANA DI RUANG RAWAT INAP RSUP DR. M.DJAMIL PADANG - Fatima Nuraini Sasmita (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2019)
Implementing nurses have a very important role in hospitals, one of which is in improving the quality of hospital services. Therefore, the hospital must prepare and have nurses who are professional and have good performance. The performance of nurses in the hospital will be more productive starting from how the hospital selects the nursing staff. This study aims to determine the relationship of selection of human resources with the productivity of the work of nurses in the inpatient RSUP Dr. M. Djamil Padang. This type of research is quantitative with cross sectional approach. The sample in this study amounted to 168 implementing nurses who were determined by using random sampling. Data analysis techniques used Chi-Square (Pearson Chi-Square) and Contingency Coefficient (C) statistical tests. The results showed the majority of implementing nurses (71%) stated the work productivity of implementing nurses in Dr. M.Djamil Padang Baik and almost half of the nurses (29%) said that the work productivity of nurses in Dr. RSUP M. Djamil Padang is not good. That most of the implementing nurses (58.9%) stated that the selection system in RSUP Dr. M.Djamil Padang Good and almost half of the implementing nurses (41.1%) stated that the selection system in Dr. M. Djamil Padang is not good, there is a significant relationship between the selection of human resources with the productivity of the working nurses in the inpatient room RSUP Dr. M. Djamil Padang. From the results of this study it is expected that the hospital can maintain the hospital recruitment selection system especially for nurses so that the hospital can maintain hospital work productivity which will have a direct impact on the quality of hospital services.